Pengaruh Skill Penyiar Radio Fatwa terhadap Minat Dengar Mahasiswa Komunikasi dan Penyiaran Islam - Saraswati Saraswati; Choiriyah Choiriyah; Mohd Aji Isnaini (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2018)
This study uses quantitative data, where the primary data sources are students of Islamic Communication and Broadcasting who are active in lectures as many as 457 students. The sample used based on simple random sampling technique was 41 students. The data obtained were analyzed using the TSR formula and Rank Spearman Correlation through SPSS 23 and Excel. The theory used in this study is the Berlo Communication Model or known as the SMCR (Sender-Message-Channel-Receiver) model. In addition, this study also uses the SOR (Stimulus-Organism-Response) theory.The results of the research conducted on 41 respondents were that Radio Fatwa's broadcasting skills were classified as medium, as well as the listening interest of Islamic Communication and Broadcasting students who were also classified as medium. In addition, researchers also found that there was a significant influence between Radio Fatwa's broadcasters' skills on the listening interest of Islamic Communication and Broadcasting students.